Temporal and Spatial Characterization of Mononuclear Phagocytes in Circulating, Pulmonary Alveolar, and Interstitial Compartments in LPS-Induced Acute Lung Injury - Li, Qi; Xiang, Guoan; Peng, Shouchun; Ji, Wenjie (Frontiers in Surgery, 2022)
Abstract Peripheral circulating monocytes and resident macrophages are heterogeneous effector cells playing a critical role in the maintenance and restoration of pulmonary integrity. However, their detailed dynamic changes in lipopolysaccharide (LPS)-induced acute lung injury (ALI) remain unclear. Here, we investigated the impact of mononuclear phagocyte cells in the development of LPS-induced ALI/Acute respiratory distress syndrome (ARDS) and described the relations between the dynamic phenotypic changes and pulmonary pathological evolution. In this study, mice were divided into two groups and intraperitoneally injected with normal saline (NS) or LPS, respectively. A serial of flow cytometry assays were performed for quantification of peripheral circulating monocytes subpopulations, detection of polarization state of bronchoalveolar lavage fluid (BALF)-isolated alveolar macrophages (AMφ) and pulmonary interstitial macrophages (IMφ) separated from lung tissues. Circulating Ly6Clow monocytes expanded rapidly after LPS challenge on day 1 and then decreased to day 7, while Ly6Chigh monocytes gradually increased and returned to normal level on the 7th day. Furthermore, the expansion of M2-like AMφ (CD64+CD206+) peaked on day 1 and remained high on the 3rd day, while the polarization state of IMφ (CD64+ CD11b+) was not influenced by LPS challenge at all time-points. Taken together, our findings show that Ly6Clow monocytes and M2-like AMφ form the major peripheral circulation and pulmonary immune cell populations, respectively. The dynamic changes of mononuclear phagocyte in three Compartments after LPS challenge may provide novel protective strategies for mononuclear phagocytes.